Two new species, Caenanthura koreana sp. nov. and Apanthura koreaensis sp. nov. (Crustacea: Isopoda: Anthuridae) from South Korea - Song, Ji-Hun; Min, Gi-Sik (Zootaxa, 2015)
Two new species of anthuroid isopods, Caenanthura koreana sp. nov. and Apanthura koreaensis sp. nov. are described from the southern and western coasts of the Korean Peninsula. A key to the species and the type locality of Caenanthura are provided. Additionally, we determined the partial sequences of the mitochondrial cytochrome c oxidase subunit 1 (CO1) from two new species.